Endothelial and cardiomyocyte PI3Kβ divergently regulate cardiac remodelling in response to ischaemic injury. Issue 8 (28th November 2018) - Chen, Xueyi; Zhabyeyev, Pavel; Azad, Abul K; Wang, Wang; Minerath, Rachel A; DesAulniers, Jessica; Grueter, Chad E; Murray, Allan G; Kassiri, Zamaneh; Vanhaesebroeck, Bart; Oudit, Gavin Y
Abstract : Aims: Cardiac remodelling in the ischaemic heart determines prognosis in patients with ischaemic heart disease (IHD), while enhancement of angiogenesis and cell survival has shown great potential for IHD despite translational challenges. Phosphoinositide 3-kinase (PI3K)/Akt signalling pathways play a critical role in promoting angiogenesis and cell survival. However, the effect of PI3Kβ in the ischaemic heart is poorly understood. This study investigates the role of endothelial and cardiomyocyte (CM) PI3Kβ in post-infarct cardiac remodelling. Methods and results: PI3Kβ catalytic subunit-p110β level was increased in infarcted murine and human hearts. Using cell type-specific loss-of-function approaches, we reported novel and distinct actions of p110β in endothelial cells (ECs) vs. CMs in response to myocardial ischaemic injury. Inactivation of endothelial p110β resulted in marked resistance to infarction and adverse cardiac remodelling with decreased mortality, improved systolic function, preserved microvasculature, and enhanced Akt activation. Cultured ECs with p110β knockout or inhibition displayed preferential PI3Kα/Akt/endothelial nitric oxide synthase signalling that consequently promoted protective signalling and angiogenesis. In contrast, mice with CM p110β-deficiency exhibited adverse post-infarct ventricular remodelling with larger infarct size and deteriorated cardiac function, which was due to enhanced susceptibility of CMs to ischaemia-mediated cell death. Disruption of CM p110β signalling compromised nuclear p110β and phospho-Akt levels leading to perturbed gene expression and elevated pro-cell death protein levels, increasing the susceptibility to CM death. A similar divergent response of PI3Kβ endothelial and CM mutant mice was seen using a model of myocardial ischaemia–reperfusion injury. Conclusion: These data demonstrate novel, differential, and cell-specific functions of PI3Kβ in the ischaemic heart. While the loss of endothelial PI3Kβ activity produces cardioprotective effects, CM PI3Kβ is protective against myocardial ischaemic injury. Graphical Abstract: